Selinda : Permainan Petak Umpet untuk Meningkatkan Self Awareness dalam Pencegahan Pelecehan Seksual pada Anak - Gita Syawla Indah Fitri; Kharisma Safitri; Rahmatul Ulfa; Rodatul Jannah; Muzhdhalifatul Azizah; Jeni Fadhila; Maya Yasmin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Cases of exposing sex are becoming increasingly common, not only attacking adults but also attacking minors. This research examines how to increase self-awareness in children by using the principles of playing seek and hide or playing hide and seek to overcome cases of sexual disclosure in early childhood (Kindergarten group). The subjects involved in this research were 16 children at Kindergarten Kartika 1-57 Bukittinggi aged 4-6 years. The research method used was experimental with a one group pretest posttest design. The results obtained in this research were that the Selinda program was proven to be effective in increasing self-awareness in students at Kindergarten Kartika 1-57 Bukittinggi.